Empowerment On Climate Change: How Community Based Organizations Serving In Growing participation from society - Friska Indria Nora; Mahfuzi Irwan (Journal of Millennial Community, 2019)
Climate change is not something scary, dangerous. Urgent, exceptional and most importantly is that climate change was not known when it happened. And the thing to do is not frightened by the climate change, but it must be to explain to the people and groups that climate change is inevitable and things to do is to minimize the impact of climate change. One of them is by not cutting down trees carelessly, can manage waste and preserve family environment such as that done by the community Pangerwangi village, Lembang, West Java. The village which has been awarded as the climate village for being able to survive and adapt to climate change .. Because the essence of Kampung climate is how the community to survive and adapt to the climate because it is people who have to adjust to the climate. And achievements that have been achieved not in spite of community participation and community-based organizations.